Mental Health of Tourism Employees Post COVID-19 Pandemic: A Test of Antecedents and Moderators - Ibrahim A. Elshaer; Alaa M. S. Azazz (European Journal of Investigation in Health, Psychology and Education, 2023)
Many people are experiencing a lack of confidence in the security of their employment due to the COVID-19 pandemic, particularly employees in the tourism sector, which has caused adverse effects on their mental health. These adverse effects involve the management of stress, anxiety and depression, that may arise from the demands of the industry. However, few studies have explored how insecurity in the workplace and financial pressure from families affects mental health and can intervene in these relationships. In this study, the aim was to investigate job insecurity as an antecedent of employees’ mental health and family financial pressures as a moderator using a sample of 475 hotel and travel industry employees. The theoretical background of the study was built upon the theories of resource conservation and effort–reward imbalance. The participants completed an online survey that measured job insecurity, family financial pressure, depression, anxiety, and stress. The collected data were subjected to PLS-SEM data analysis. The findings of this study reveal that job insecurity had a significant influence on depression, anxiety, and stress among tourism employees, and family financial pressure worsened the negative consequences of job insecurity on mental health. This research highlights the significance of addressing the mental health of employees in the tourism sector after the COVID-19 pandemic, as well as the crucial role played by family financial pressures. The findings of this study highlight the importance of addressing job insecurity in the tourism industry and its impact on employees’ mental health. This could involve implementing policies and practices that enhance job security, such as providing more stable work schedules, better benefits packages, and greater opportunities for professional development. The results also underscore the need to take into account the role of family financial pressure in moderating the impact of job insecurity on mental health. Practitioners and policymakers in the tourism industry should consider ways to alleviate financial pressure on employees and their families, such as offering assistance programs, flexible work arrangements, and supportive company policies.